2006
DOI: 10.1177/039139880602900408
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistant Pathogenic Bacteria and Their Resistance Genes in Bacterial Biofilms

Abstract: Biofilm-forming bacteria are ubiquitous in the environment and also include biofilm-forming pathogens. Environmental biofilms may form a reservoir for risk genes and may act as a challenge for human health. Examples of the health relevance of biofilms are the increase in antibiotic resistant bacteria hosted in biofilms in hospital and environment and consequently the interaction of these bacteria with human cells, e.g. in the immune system. Although data concerning the occurrence and spread of resistant bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Frequent contact of the bacteria with even minor concentrations of antibiotics can cause the occurrence or persistence of resilient bacteria strains [17][18][19][20][21]. Earlier research showed that the maximum of the antibiotics in the environment showed straight hazardous properties [22,23] and bad effects [24][25][26].…”
Section: Sources Of Antibiotics In the Environmentmentioning
confidence: 99%
“…Frequent contact of the bacteria with even minor concentrations of antibiotics can cause the occurrence or persistence of resilient bacteria strains [17][18][19][20][21]. Earlier research showed that the maximum of the antibiotics in the environment showed straight hazardous properties [22,23] and bad effects [24][25][26].…”
Section: Sources Of Antibiotics In the Environmentmentioning
confidence: 99%
“…The most common explanation of the bacterial biofilm durability is the mechanism of secretion of antibiotic-degrading enzymes, which reduces the possibility of penetration of the antimicrobial substances to the lower layers of cells (Stewart and Costerton 2001;Obst et al 2006;Chaignon et al 2007;Hoiby et al 2010;Banerjee et al 2011) . Another common argument is based on emerging multi-layer construction of the structure of the biofilm, which also impedes the penetration of antimicrobial substances (Etienne et al 2005;An et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Antibiotics can be efficacious against planktonic (free living) pathogens but are quite often poorly effective against the bacteria organized in community which can increase antibiotic resistance by up to 1000 fold [43]. Biofilm structured bacteria develop a multifactorial mechanism of resistance to antibiotics, but the most important factor of tolerance is due to the slow growth and low metabolic activity of bacterial cells in the internal layer of community, so they are intrinsically resistant to conventional antibiotics which target dividing and metabolically active cells.…”
Section: Antimicrobial Biofilm Peptidesmentioning
confidence: 99%